The future of sports delivery in Australia NBN multicast, IPTV and the role of the ISPs - McCosker, Anthony (Journal of Telecommunications and the Digital Economy, 2013)
Where lucrative media rights deals for sports content currently lie primarily with pay TV and free to air (FTA) broadcasters, Internet Service Providers (ISPs) entering the content delivery market through partners such as Fetch TV may be better placed to compete for distribution rights to sporting and other live events. In response to this shifting environment this paper outlines the technological capacities of NBN-based multicast Internet Protocol Television (IPTV), and examines public comment and interview data from ISPs, sports organisations and NBN Co. regarding their intentions for IPTV delivery. This paper begins with the assumption that diversity in these emerging media forms remains important as ISPs enter the media content market. We demonstrate, however, that despite the emergence of NBN-based technologies, diversity in sports content distribution cannot be assumed. The paper points toward the important role that regulators, such as the ACCC, have in maintaining diversity and competition in IPTV services.